INFLUENCE OF VOLTAGE DEVIATION ON THE TECHNOLOGICAL AND ENERGY CHARACTERISTICS OF FEED MIXER - Sinyavsky, A.; Savchenko, V.; Bunko, V. (Енергетика і автоматика, 2016)
The effect of voltage deviation on the angular speed, technological and energy characteristics of the feed mixer are conducted. The dependences of uneven mixing and specific consumption of electric on voltage are established.